2007
DOI: 10.1111/j.1750-3639.2007.00098.x
|View full text |Cite
|
Sign up to set email alerts
|

Maturation and Localization of Macrophages and Microglia During Infection with a Neurotropic Murine Coronavirus

Abstract: Macrophages and microglia are critical in the acute inflammatory response and act as final effector cells of demyelination during chronic infection with the neutrotropic MHV-JHM strain of mouse hepatitis virus (MHV-JHM). Herein, we show that "immature" F4/80(+)Ly-6C(hi) monocytes are the first cells, along with neutrophils, to enter the MHV-JHM-infected central nervous system (CNS). As the infection progresses, macrophages in the CNS down-regulate expression of Ly-6C and CD62L, consistent with maturation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 51 publications
3
51
0
Order By: Relevance
“…Furthermore, the majority of the CD11b ϩ infiltrating cells had the Ly-6C hi phenotype ( Fig. 1E), which was recently established as a reliable marker of blood-derived macrophages (1,99,100). Taken together, these data suggest that the CNS of me/me mice displays a dramatic increase in the number of infiltrating macrophages (7,41,58,88).…”
Section: Resultssupporting
confidence: 55%
“…Furthermore, the majority of the CD11b ϩ infiltrating cells had the Ly-6C hi phenotype ( Fig. 1E), which was recently established as a reliable marker of blood-derived macrophages (1,99,100). Taken together, these data suggest that the CNS of me/me mice displays a dramatic increase in the number of infiltrating macrophages (7,41,58,88).…”
Section: Resultssupporting
confidence: 55%
“…The Ly-6C hi monocytes migrated to the inflamed/necrotic area and subsequently differentiated into mature macrophages. This process required downregulation of Ly-6C expression and an increase in the expression of the mature macrophage marker F4/80 (2,38). In the present study, we demonstrated that the loss of Foxm1 in a myeloid lineage reduced numbers of Ly-6C lo /F4/80 hi mature macrophages at 72 h after liver injury, coinciding with delayed liver repair.…”
Section: Discussionmentioning
confidence: 54%
“…Whereas neutrophils, characterized as CD45 hi Ly6C low F4/80 Ϫ Ly6G hi (6,45), represented a small percentage of CNS infiltrating leukocytes following infection (Fig. 1A) (ϳ6% at day 3 p.i.…”
Section: Inflammatory Monocytes Dominate Cns Inflammatory Cells Earlymentioning
confidence: 99%